DETERMINATION OF PROTEIN CONTENT IN MUNG BEAN YIELD UNDER THE CONDITIONS OF FERGANA REGION - Mirzayeva Mutabar Azamovna; Teshaboyev Nodirbek Ikromjonovich (Modern American Journals, 2025)
The article presents data on the influence of sowing dates and rates on yield and biologically valuable traits in the conditions of typical gray soils of the Fergana region. In the conditions of typical gray soils of the Fergana region, when mung beans were sown as a repeated crop in the third decade of June at a rate of 14 kg per hectare, the bulk density of the soil in the arable and sub-arable layers decreased by 0.03 g/cm3 compared to the variants planted at a rate of 10 kg per hectare, and soil porosity increased by 1.0-1.2%. It was also observed that with an increase in the sowing rate, the content of nitrate nitrogen increased.
Keywords: Typical gray soil, repeated cropping, mung bean, planting date and criteria, root and shoot residues, agrophysical properties of soil, protein.